A Comparative Study of Emotional Intelligence and Learning Outcomes of Full-Day and Boarding School Students - Sufah, Faila; Sukiman, Sukiman (Southeast Asian Journal of Islamic Education, 2023)
This study aimed to determine the difference in emotional intelligence and Islamic religious education learning outcomes of full-day and boarding school seventh-grade students at Diponegoro Junior High School, Depok, Yogyakarta, in the 2022/2023 academic year. A quantitative approach with ex post facto design (causal-comparative) was employed. The population was all seventh-grade students, namely 180 students. 32 full-day and 32 boarding school students were selected as samples using a purposive sampling technique for their low Islamic Religious Education learning outcomes. Data were collected through the distribution of questionnaires and the administration of tests. These data were then analyzed using hypothesis testing with independent sample t-tests and Mann-Whitney tests. The results showed that first, there is a difference in the emotional intelligence of full-day and boarding school students, as evidenced by the p-value of 0.036 <00.5, which is shown from the average value of emotional intelligence of full-day school students of 77.469 while boarding school students of 81.938. Second, there is a difference in Islamic religious education learning outcomes of full-day and boarding school students, as evidenced by the p-value of 0.001 <0.05, which is indicated by the average value of Islamic religious education learning outcomes of full-day school students of 77.813, while boarding school students of 90.000. This study contributes to developing a scientific theory about the difference in emotional intelligence and learning outcomes of full-day and boarding school students. Particularly for low-achiever students, a boarding school environment with good management and learning quality might better influence their emotional intelligence and learning outcomes.